Open Access Monographs: Myths, Truths and Implications in the Wake of UKRI Open Access Policy - Fathallah, Judith (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2022)
The UK Research and Innovation funding council announced its latest Open Access Policy on August 6, 2021. This policy applies to all UKRI funded research, and thus constitutes a significant move towards OA as an academic standard. For the first time in the UK, OA is to be mandated for academic books – this means that both monographs and edited chaptered books must be published Open Access from January 2024, though a 1 year embargo is permissible. As the infrastructures, business models and workflows supporting OA book publishing are currently lagging behind journals, especially in the Arts and Humanities, many researchers and institutions have responded to the policy with some consternation, even whilst supporting the aims and ethics of OA publishing. This article explores some of these apprehensions and questions raised by institutions, academics and by librarians regarding OA book publishing in a UK context, especially regarding funding and sustainability. It aims to dispel certain myths around OA book publishing in general, particularly the notion that Book Processing Charges are a necessary or even desirable element. The article then presents some of the varied models and systems currently in use and development, particularly the work of the UKRI/Research England funded COPIM project (Community- Led Open Access Infrastructures for Monographs), one of the aims of which is to build ways of delivering more sustainable revenue sources to OA publishers. It focuses in particular a key and soon to be launched output of the project: the Open Book Collective.